Attractive solutions efficiency in capturing Zaprionus indianus Gupta,1970 (Diptera: Drosophilidae) in Ficus carica L. (Moraceae) orchard in Santa Maria, Rio Grande do Sul, Brazil - Pasini, Mauricio Paulo Batistella; Link, Dionísio; Schaich, Gabriel (ENTOMOTROPICA, 2011)
This study aimed to determine the response of Zaprionus indianus Gupta, 1970 (Diptera: Drosophilidae) to different attractive solutions based on Ficus carica L., Psidium guajava L. and Butia capitata (Mart) Becc. juice diluted in water. The work was conducted at the Fruit Trees Sector from the Colégio Politécnico of the Universidade Federal de Santa Maria, Brazil, from February 25th to April 24th of 2010 in an orchard of fig. Plastic bottles were used as traps, and as attractants, were used pure F. carica, P. guajava and B. capitata juice and F. carica juice with a glucose solution, all diluted in water, amounting 200 ml of attractive solution for each bottle. Statistical analysis showed that F. carica juice diluted in water in the concentration of 50 % had the highest catch rates when compared with the other treatments and is recommended for controlling and monitoring Z. indianus. The rest of the attractants can be used as an alternative for monitoring. The highest catch levels are not associated with production peaks from the fig orchard. In the different attractants used, the pH, Brix degree and volume values correlated negatively with the number of fig fly adults captured.